Type 1 Innate Lymphoid Cells Are Proinflammatory Effector Cells in Ischemia-Reperfusion Injury of Steatotic Livers - Kang, Jiman; Liggett, Jedson R.; Patil, Digvijay; Ranjit, Suman; Loh, Katrina; Duttargi, Anju; Cui, Yuki; Oza, Kesha; Frank, Brett S.; Kwon, DongHyang; Kallakury, Bhaskar; Robson, Simon C.; et al. (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs), the most recently described family of lymphoid cells, play fundamental roles in tissue homeostasis through the production of key cytokine expression. Group 1 ILCs, comprising conventional natural killer cells (cNKs) and type 1 ILCs (ILC1s), have been implicated in regulating immune-mediated inflammatory diseases, but the role of ILC1s in nonalcoholic fatty liver disease (NAFLD) and ischemia-reperfusion injury (IRI) is unclear. Here, we investigate the role of ILC1 in a high-fat diet (HFD) murine model of partial warm IRI. We demonstrate that hepatic steatosis results in more severe IRI compared to non-steatotic livers. We further elicit that HFD-IRI mice show a significant increase in the ILC1 population, whereas the cNK population is unchanged. Since ILC1 and cNK are major sources of proinflammatory IFN-γ and TNF-α, we measured the level of ex vivo cytokine expression in normal diet (ND)-IRI and HFD-IRI conditions. We find that ILC1 in HFD-IRI mice produced significantly more IFN-γ and TNF-α when compared to ND-IRI. To assess whether ILC1s are key proinflammatory effector cells in hepatic IRI of fatty livers, we studied both Rag1−/− mice, which possess a substantial population of ILC1s, and newly generated Rag1−/− Tbx21−/− double knockout (Rag1-Tbet DKO) mice, which lack type 1 ILCs, under HFD IRI conditions. Importantly, HFD Rag1-Tbet DKO mice show significant protection of hepatic injury upon IRI compared to Rag1−/− mice, suggesting that Tbet-expressing ILC1s play an important effector role in hepatic IRI of fatty livers